Penerapan Teknologi Pemangkasan, Pemupukan, Panen Sering, Dan Sanitasi (P3S) Dalam Pengendalian Hama Penggerek Buah Kakao (PBK) Di KSU Plea Puli, Desa Bloro, Kecamatan Nita - Fransiska Dua Bertha (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2023)
Cocoa plants are one of the plantation crops that are a source of income for farmers in Indonesia. In cocoa farming, various problems are faced by farmers in increasing the productivity of cocoa plants. The main factors that become problems in cocoa cultivation are pests and diseases. Pests that often attack kakao plants are Cocoa Fruit Borer (PBK). The purpose of this community service activity is to empower the community in Bloro Village, Nita District, Sikka Regency in applying P3S technology (pruning, fertilizing, frequent harvesting, and sanitation) in PBK pest control. The methods applied by the PKM Team include socialization/counseling, and training on the application of P3S technology. The results of the activity showed thatthe activity went smoothly. This activity is able to provide knowledge to the community in applying P3S technology in PBK pest control on cocoa plants. Obstacles that arise at the implementation stage can be overcome by monitoring, evaluation, and mentoring methods. The application of technology implemented produces P3S technology as PBK pest control which can increase the productivity of cocoa plants.